BHA‐CS: A novel cognitive composite for Alzheimer's disease and related disorders. Issue 1 (21st June 2020) - Tsoy, Elena; Erlhoff, Sabrina J.; Goode, Collette A.; Dorsman, Karen A.; Kanjanapong, Suchanan; Lindbergh, Cutter A.; La Joie, Renaud; Strom, Amelia; Rabinovici, Gil D.; Lanata, Serggio C.; Miller, Bruce L.; Tomaszewski Farias, Sarah E.; et al.
Abstract: Introduction: Composite scores based on psychometrically rigorous cognitive assessments are well suited for early diagnosis and disease monitoring. Methods: We developed and cross‐validated the Brain Health Assessment‐Cognitive Score (BHA‐CS), based on a brief computerized battery, in 451 cognitively normal (CN) and 399 cognitively impaired (mild cognitive impairment [MCI] or dementia) older adults. We investigated its long‐term reliability and reliable change indices at longitudinal follow‐up (N = 340), and the association with amyloid beta (Aβ) burden in the CN subgroup with Aβ positron emission tomography (N = 119). Results: The BHA‐CS was accurate at detecting cognitive impairment and exhibited excellent long‐term stability. Reliable decline over one year was detected in 75% of participants with dementia, 44% with MCI, and 3% of CN. Among CN, the Aβ‐positive group showed worse longitudinal performance on the BHA‐CS compared to the Aβ‐negative group. Discussion: The BHA‐CS is sensitive to cognitive decline in preclinical and prodromal neurodegenerative disease.